2004
DOI: 10.1023/b:maci.0000037650.83572.81
|View full text |Cite
|
Sign up to set email alerts
|

How Children with Special Health Care Needs Affect the Employment Decisions of Low-Income Parents

Abstract: These results indicate that only a specific subset of children with special needs present difficulties for low-income parents' work. This suggests that policies to help low-income single parents of children with disabilities move into work should target this specific subset of children with special health care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 8 publications
2
46
0
Order By: Relevance
“…Although the Screener questions were not repeated in subsequent years, efforts have been made to develop an algorithm to replicate the CSHCN Screener based on core and sample child questions (Davidoff 2004).…”
Section: National Health Interview Survey (Nhis)mentioning
confidence: 99%
See 3 more Smart Citations
“…Although the Screener questions were not repeated in subsequent years, efforts have been made to develop an algorithm to replicate the CSHCN Screener based on core and sample child questions (Davidoff 2004).…”
Section: National Health Interview Survey (Nhis)mentioning
confidence: 99%
“…For the most part, survey measures of disability, functional limitation, or health consequences have avoided one aspect of disability that defies operationalization-increased risk (see Loprest and Davidoff 2004). Although the MCHB definition of children with special health care needs includes children who are at risk for having spe-cial health care needs, the CSHCN Screener does not account for children who do not currently have SHCN.…”
Section: Examples Of Health Findings Using Survey Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In families who spend 11 or more hours a week caring for their CSHCN, 19% live in poverty compared to 4% living in families with higher incomes (HHS, 2007). However, Loprest & Davidoff (2004) found that families whose CSHCN had activity limitations were significantly less likely to work and worked fewer hours. Families caring for children with more severe conditions at home were more likely to report financial and employment problems (Kuhlthau et al, 2005;Rupp & Ressler, 2009;Okumura, Van Cleave, Gnanasekaran & Houtrow, 2009).…”
Section: Families With Children With Special Health Care Needsmentioning
confidence: 92%